Experimental Study on Shield Tunneling Control in Full Section Water-Rich Sand Layer of Collapsible Loess - Yuan Mei; Xinyue Zhang; Shumin Zhang; Rong Wang; Tong Yang; Yuhang Zhang (Geofluids)
Taking China’s first application of domestic shield tunneling in a water-rich sand layer for crossing a high-speed railway as research background, the influence of changes in the shield tunneling parameters on ground settlement is analyzed based on field tests, and a construction control method suitable for shield tunneling under a risk source in a water-rich sand layer is proposed. The test results show that the use of 10% sodium bentonite as the soil modifier for soil pressure balance shield tunneling into the water-rich sand layer has advantages, while adding 50% loess into the bentonite slurry in the gravel sand layer can greatly improve the impermeability of the soil; the settlement of soil can be effectively reduced by using the special segment with grouting holes for deep grouting and applying the adaptive transformation of the shield cutter. Based on the statistical analysis results, a reasonable range for the cutter head torque, cutter head speed, chamber pressure, bentonite injection volume, and advanced speed in the water-rich sand layer can provide a construction control basis for similar projects and provide data support for the compilation of relevant specifications.